Hubungan Pola Makan dan Stres dengan Kejadian Dispepsia pada Siswa di SMP Negeri 2 Karang Intan - Elsi Setiandari Lely Octaviana; Noorhidayah Noorhidayah; Aulia Rachman (HB PRESS, 2021)
Dyspepsia is a type of non-communicable disease that occurs not only in Indonesia but also in the world. Dyspepsia is a term commonly used for a syndrome or a collection of symptoms or complaints in the form of pain or discomfort in the gut, nausea, bloating, vomiting, belching, feeling full quickly, and a full stomach. The high incidence of dyspepsia in adolescents is mostly caused by irregular dietary patterns. Dyspepsia can also be caused by several factors, including stress. Stress can affect gastrointestinal function and trigger complaints in healthy people, one of which is dyspepsia. This condition is due to excess stomach acid and a decrease in gastric contractility that precedes complaints of nausea after a central stress stimulus. From the results of the initial interviews conducted on 15 students of State Junior High School 2 Karang Intan, 9 of them had dyspepsia. This study aimed to determine the relation of dietary patterns and stress to the incidence of dyspepsia in students of State Junior High School 2 Karang Intan. This quantitative research used a cross-sectional study design. The number of samples was 56 people. The data were collected using a questionnaire and analyzed using the chi-square test. The results showed that 56 people (55,4%) met the dyspepsia criteria with a p-value of 0.001 (p <0.05), and 21 people had stress (80.8%) with a p-value of 0.001 (p<0.05).